Beyond performance : how great organizations build ultimate competitive advantage - Keller, Scott, 1972-; Price, Colin (Hoboken, N.J. : Wiley, 2011)
"What makes your company great today, however, won't necessarily make it great tomorrow. Evolving is critical to long-term corporate performance and health. Humankind's greatest invention isn't the wheel, it is organization: people working together towards a goal that is beyond what can be achieved by the sum of individuals acting alone. As each generation finds better and better ways of working together, we perform at levels that previous generations could never have imagined. On top of long term trends like cost-free availability of information and deriving differentiation by creating an experience, the world appears to be emerging from the most profound and far-reaching economic crisis since the great depression of the 1930's. And five other factors will continue to drive global change: the historic shift in economic growth from the developed to the developing world; an unprecedented imperative for mature economics to raise productivity to preserve living standards; the rise of new networks of communication and trade; a profound challenge in balancing economic growth and environmental sustainability; and an expanded role for the state in regulating markets. For organizations to not only be excellent but stay excellent, companies need to respond to these challenges with tact and understanding that with the right techniques, change can be driven to a company's advantage. If you are a leader of people who wants to change things for the better, this book is for you. If you want to leave a profound and lasting legacy in your organization and the stakeholder it serves, this book will help you do so"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Organizational behavior; Corporate culture; Performance